Service access and perceptions for Somali Australian migrants at risk of autism. Issue 1 (6th March 2017) - Abdullahi, Ifrah; Kruger, Estie; Tennant, Marc
Abstract : Purpose: The purpose of this paper is to examine the service accessibility of Somali Australians suffering Autism Spectrum Disorder (ASD) by using both quantitative and qualitative methods. Design/methodology/approach: Using Geographic Information System (GIS) and the 2011 census data a total of 19, 178 people reporting Somali ancestry were mapped to SA1 level with most being in the three capital cities of original migration; Sydney, Melbourne and Perth. Findings: Access to primary services pertinent to ASD was measured using the GIS software, some 15 per cent of these cities Somali children were within 500 m of a General practice and 89 per cent within 2, 000 m. A quarter of children were within 2, 000 m of a speech pathology service access point and nearly a third (31 per cent) within 2, 000 m of a psychologist. Qualitative analysis found a quite negative perspective on mental illness and ASD within the community with 85 per cent of respondents reporting a "Bad" perception of ASD within the community. Research limitations/implications: Clearly, the opportunity these data provide is to develop service models targeting need and changing perspectives of ASD within an at risk community. Originality/value: This is the first time in Australia that issues of service access (health) for Autism suffers and their families has been analysed in a detailed geographic manner.